A Review of Hypothesized Determinants Associated with Bighorn Sheep (Ovis canadensis) Die-Offs. (29th March 2012) - Miller, David S.; Hoberg, Eric; Weiser, Glen; Aune, Keith; Atkinson, Mark; Kimberling, Cleon
Abstract : Multiple determinants have been hypothesized to cause or favor disease outbreaks among free-ranging bighorn sheep ( Ovis canadensis ) populations. This paper considered direct and indirect causes of mortality, as well as potential interactions among proposed environmental, host, and agent determinants of disease. A clear, invariant relationship between a single agent and field outbreaks has not yet been documented, in part due to methodological limitations and practical challenges associated with developing rigorous study designs. Therefore, although there is a need to develop predictive models for outbreaks and validated mitigation strategies, uncertainty remains as to whether outbreaks are due to endemic or recently introduced agents. Consequently, absence of established and universal explanations for outbreaks contributes to conflict among wildlife and livestock stakeholders over land use and management practices. This example illustrates the challenge of developing comprehensive models for understanding and managing wildlife diseases in complex biological and sociological environments.